A comparative study of heat-treatment effects on high-strength ductile cast irons weldments - Silva, Francisco José Gomes da (2020)
Ductile cast irons have known significant developments, closely following the evolution in mechanical strength recorded in other metal alloys. In fact, the chemical composition and treatments that ductile cast irons can currently be subjected to, give them mechanical strength far superior to the ductile cast irons that existed three decades ago, with rupture stresses in the order of 500 MPa and even higher. These properties combined with the fact that it is easy to manufacture parts with an almost final shape, makes these alloys highly sought after in some types of industry, such as the automotive industry. Due to the high content of carbon and other alloy elements with identical effects, welding is not a process that is seen as viable for the manufacture of parts in this type of alloys. However, the same is no longer the case in terms of repair, where welding can play a key role. Through a comparative study, this work intends to show that there is no single way to improve the mechanical properties in the welding of this type of alloys, and that each alloy should be properly studied in order to obtain the best results. In this case, the heat treatments applied to ductile cast iron with an ultimate tensile strength of 450 MPa and 700 MPa from the same manufacturer are compared, making it clear that to achieve the best results in terms of mechanical resistance, it is necessary to follow different routes, that is, choose to preheating or post-heating treatments, depending on the microstructure of the alloy used. Thus, the results obtained intend to show the mechanisms in which treatment is actually acting on the alloy, promoting greater efficiency of the joint and having been achieved interesting results at this level.